Modulation of Hepatic Functions by Chicory (Cichorium intybus L.) Extract: Preclinical Study in Rats - Lubov V. Krepkova; Alexandra N. Babenko; Svetlana V. Lemyaseva; Olga L. Saybel; Catherine M. Sherwin; Elena Y. Enioutina (MDPI AG, 2023)
The liver is important in detoxifying organisms from xenobiotics, supporting immune functions, and metabolizing lipids and glucose. In addition, a growing number of drug-induced liver injuries and diseases associated with liver dysfunction make the development of phytodrugs targeting multiple liver functions particularly crucial. Therefore, we investigated the effects of a novel chicory extract prepared from aerial parts of the wild Cichorium intybus L. plant (CE) on liver enzymes and on lipid and glucose metabolism in rats with acute liver injury or hyperlipidemia. A single subcutaneous injection of mercury chloride induced an acute liver injury. Hyperlipidemia was induced by a single intraperitoneal injection of Tween-80 or by feeding rats with cholesterol and mercazolil for 28 days. Under varying regimens, the experimental rats received 100 mg/kg b.w. or 500 mg/kg b.w. of CE. CE treatment ameliorated acute liver injury by reducing liver enzyme activity, bilirubin, glucose, and lipid levels. Treatment of hyperlipidemic rats with CE effectively reduced serum lipid and glucose levels. The data obtained in this study suggest that chicory-based phytodrugs may be used to effectively treat acute liver injury and for the prophylaxis or treatment of diseases such as hyperlipidemia, type 2 diabetes, and metabolic syndrome. Clinical trials are needed to prove the effectiveness of chicory extract in human patients.